Värdebaserat ledarskap - Ur befälhavarens perspektiv - Westring, Jakob; Melipillan, Amaro (My University, 2017)
A well-functioning organization onboard is a must aboard a ship, and all too often, we have seen an organization that lack in teamwork and communication between the master, employees and shore management. A business that lacks a consensus and agreement between top management and the master. Value-based leadership could lead to a greater consensus within the organization, its members and groups between. Dan Sten Olsson, Stena AB's owner and CEO is a great example of value-based leadership. He believes that their business is based on a clear set of core values that is an important part of the company culture. Within the company the master has a middle management role where he is expected to follow management instructions and have a great role in spreading these ideological values on board. The purpose of this study, based on the master's perspective, is to examine how Stena AB's established principles, convictions and basic values permeate the master's interaction with the shore management and the on board crew. The study is based on Stena AB's principles, convictions and basic values, organization- and leadershiptheory with a focus on values-based leadership and corporate culture. Two masters and three subordinate employees within Stena Line shipping company were interviewed and then the result analyzed. The results show a unified view of the business where the respondent´s view in great part consist with Olsson's principles, convictions and basic values with some shortcomings.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport